2015
DOI: 10.1111/jpi.12232
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of melatonin synthesis and degradation genes in rice leaves in response to cadmium treatment

Abstract: We investigated the expression patterns of genes involved in melatonin synthesis and degradation in rice leaves upon cadmium (Cd) treatment and the subcellular localization sites of melatonin 2-hydroxylase (M2H) proteins. The Cd-induced synthesis of melatonin coincided with the increased expression of melatonin biosynthetic genes including tryptophan decarboxylase (TDC), tryptamine 5-hydroxylase (T5H), and N-acetylserotonin methyltransferase (ASMT). However, the expression of serotonin N-acetyltransferase (SNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
138
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(162 citation statements)
references
References 49 publications
22
138
1
1
Order By: Relevance
“…In agreement with our finding, melatonin-deficient tomatoes were less protected against abiotic stress when compared to the wild type tomato41, whereas melatonin-rich plants had an improved ability to withstand such challenges29. Accumulation of endogenous melatonin has been suggested to be an adaptive response in plants under cold stress42. Treatment with exogenous melatonin significantly increased endogenous melatonin content during cold treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our finding, melatonin-deficient tomatoes were less protected against abiotic stress when compared to the wild type tomato41, whereas melatonin-rich plants had an improved ability to withstand such challenges29. Accumulation of endogenous melatonin has been suggested to be an adaptive response in plants under cold stress42. Treatment with exogenous melatonin significantly increased endogenous melatonin content during cold treatment.…”
Section: Discussionsupporting
confidence: 90%
“…These data raise many questions regarding the physiological roles of melatonin and 2‐hydroxymelatonin in plants as well as in animals. The known roles of melatonin appear not to be attributable to 2‐hydroxymelatonin, because, unlike melatonin, 2‐hydroxymelatonin is not active as a signaling molecule mediating defense responses in Arabidopsis . However, we cannot rule out the possibility that the pathophysiological roles of 2‐hydroxymelatonin in other plant species such as rice and apple may be different from those observed in Arabidopsis .…”
Section: Discussionmentioning
confidence: 90%
“…Unlike the other heavy metal pollutions, Cd is a non-essential nutrient, and seriously affects plant growth and development. Recently, Cd has been reported to regulate MLT content in rice leaves by coordinating the synthesis and degradation genes of MLT (Byeon et al, 2015). And then Hasan et al found, exogenous application of MLT could mitigate phytotoxicity induced by Cd stress in Solanum lycopersicum L., by modulation of phytochelatins biosynthesis, vacuolar sequestration, and antioxidant potential (Hasan et al, 2015).…”
Section: Resultsmentioning
confidence: 99%